Implementasi Pendidikan Agama Islam Berwawasan Lingkungan (Adiwiyata) Di Smp Negeri 2 Lamongan - Rokim Rokim (Akademika, 2023)
This research is motivated by the rampant environmental damage and the many natural disasters that can harm the ecosystem, this research is expected to form a generation that is aware and cares about environmental sustainability. This research is dIscussed about the implementation of environmentally sound Islamic religious education (Adiwiyata) at Lamongan 2 Public Middle School, and the inhibiting and supporting factors of environmentally sound Islamic religious education (Adiwiyata) at Lamongan 2 Public Middle School, this study uses a type of qualitative research, in which in this qualitative method the data collected comes from interviews, observation and documentation. The collected data were analyzed using descriptive analysis techniques. The results of this study are first, the implementation of environmentally sound Islamic religious education (Adiwiyata) at SMP Negeri 2 Lamongan with innovations made to adjust policies through the curriculum system, namely learning Islamic religious education integrated with learning environmental education (PLH), second through approaches students, abbreviated as "MaHaDanan". Second, the supporting factors for this activity are the existence of various adequate facilities, the availability of professional teaching staff, the positive response, the motivation, the interest of students in learning, the awareness of some school members, the existence of a green team community and the existence of a reward system. and punishment. While the inhibiting factors are the awareness of some school members about the importance of preserving the environment, the lack of members of the green team community, and the laziness of students. The recommendation of this research is the importance of instilling genuine intentions and cultivating to continue to maintain a clean environment, provide motivation, increase the number of green team members, and increase enthusiasm and participation from school members so that they can have a positive impact on the surrounding environment.